URGENSI SUPERVISI KEPALA MADRASAH UNTUK MATA PELAJARAN BAHASA ARAB - Qodir, Abdul (Al Tadib : Jurnal Ilmu Pendidikan, 2014)
Implementation of curriculum 2013 closely connected to the teachers and other education personnel, such as clerical, laboratory assistants, technicians and librarians. In order to run properly, then the headmaster should give guidance on the performance of teachers and other education personnel. supervision is a monitoring the activities of a specific nature, which has run the program and supervision not only supervise but provide help repair problems and motivate teachers to perform tasks better. It is the implementation of the activities of the Arabic language, both in the MI, MTs, and MA. However, there are still problems, it can not be separated from a variety of reasons including: 1) the educational background of late headmaster 2) lack of experience headmaster, and 3) the Arabic language teacher education is not in accordance with the qualifications of teaching subjects. At the end of the head of the educational reality MI, MTs, and MA is undergraduate (S1), little has been completed the graduate program (S2) with a major in almost all Islamic education and there is also that of other religious majors even exist that of the general department. It is clear there are difficulties experienced by the headmaster in the processes of supervision.Keywords: Supervision, Arabic, Curriculum